What you learn from your children (Journal of Parents and Teachers, 1996)
A mother reflects on what she has learned from her three children, highlighting the importance of independence, the need for support and joy in family life. She identifies three fundamental pillars: respect, emotional support and forgiveness. She highlights the need to observe and reflect on interactions to improve coexistence.
Keywords: reflection; independence; support; joy